Quality Management Patterns in Islamic Education to Enhance Students' Competencies - Neka Zulwiddi; Zulfani Sesmiarni; Damarkunsi Maja Sius (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Quality Management Patterns in Islamic Education to Enhance Students' CompetenciesObjective: This study aims to explore the pattern of quality management in Islamic education and analyze how its implementation can improve student competence with a focus on strengthening Islamic values, integrated curriculum, teacher competence as a role model, and Islamic value-based evaluation. Methods: This research adopts a descriptive qualitative approach. The data sources for this research consist of primary data and secondary data. Data analysis in this study follows the Miles and Huberman model. The research employs several techniques to ensure data validity, such as source, technique, member checking, and audit trail triangulation. Results: Integrating Islamic values in curriculum and learning can create an Islamic environment and support the development of students' character. Conclusion: High teacher competence as the main role model is also important in improving the quality of Islamic education. Islamic value-based evaluation also plays a role in measuring overall competency achievement. Contribution: This research contributes an innovative approach to improving student competencies through quality management based on Islamic values.IINDONESIAN: Pola Manajemen Mutu dalam Pendidikan Islam untuk Meningkatkan Kompetensi SiswaTujuan: Penelitian ini bertujuan untuk menggali pola manajemen mutu dalam pendidikan Islam dan menganalisis bagaimana penerapannya dapat meningkatkan kompetensi siswa dengan fokus pada penguatan nilai-nilai Islam, kurikulum terintegrasi, kompetensi guru sebagai teladan, dan evaluasi berbasis nilai Islam. Metode: This research adopts a descriptive qualitative approach. The data sources for this research consist of Primary data dan Secondary data. Data analysis in this study follows the Miles and Huberman model. To ensure data validity, the research employs several techniques source, Technique, Member checking and audit trail triangulation. Hasil: pengintegrasian nilai-nilai Islam dalam kurikulum dan pembelajaran dapat menciptakan lingkungan yang Islami dan mendukung perkembangan karakter peserta didik. Kesimpulan: kompetensi guru yang tinggi sebagai teladan utama juga menjadi faktor penting dalam meningkatkan mutu pendidikan Islam. Evaluasi yang berbasis nilai Islam turut berperan dalam mengukur pencapaian kompetensi secara menyeluruh. Kontribusi: Penelitian ini memberikan kontribusi pendekatan inovatif untuk meningkatkan kompetensi siswa melalui manajemen mutu berdasarkan nilai-nilai Islam.